EFEKTIFITAS PELAYANAN HOME CARE PADA PERAWATAN PALIATIF PENDERITA PENYAKIT KRONIS: KANKER - ERIDA FADILA (NHM PRESS, 2021)
Both In children and adults, chronic diseases cannot be cured, one of which is cancer, where the treatment for this disease is not optimal because it is still rare for patients who can fully recover. So the application of palliative home care is shown to improve patients' quality of life and provide support to families and increase family independence in dealing with problems related to the patient's condition by preventing and reducing suffering. The aim is to determine the effectiveness of palliative home care services for patients with chronic diseases: cancer. The search for article data sources was carried out through the Crossref database, GoogleScholar, and Mendeley (2011-2021) to retrieve articles published in Indonesian. Keywords related to home care, palliative care, and chronic disease were used in the search for related subjects. Inclusion study design using Literature Review. This shows that the level of effectiveness of palliative care carried out at home (60%) and the level of effectiveness of palliative care carried out in the hospital (40%). Palliative home care is considered effective in improving quality of life and increasing preparation for dignified death as well as increasing family independence in helping care. The application of Home care is very much needed in care because the support and role of the family are needed in nursing actions besides the costs incurred will be cheaper, provided that it does not require treatment, close supervision, special measures, or special equipment.